Cancer of Unknown Primary origin in the genomic era: Elucidating the dark box of cancer. Issue 7 (July 2015) - Economopoulou, Panagiota; Mountzios, Giannis; Pavlidis, Nicholas; Pentheroudakis, George
<x xml:space="preserve">Abstract</x> Highlights Gene expression profiling (GEP) assays assign Cancer of Unknown Primary (CUP) cases to the most likely tissue of origin. A survival benefit in CUP patients managed with tissue-specific antineoplastic therapy after use of a GEP assay is unproven. There is no consensus on the most cost-effective way to incorporate the GEP CUP assays in the current diagnostic algorithm. The search for a CUP molecular signature responsible for its atypical behavior has not been done systematically. Regarding targeting, the assumption that the same gene mutation matters in the same way across tumor types is unproven.